The intuitive foundations of philosophical self-establishing - Radzioch, Lech (Folia Philosophica, 2005)
The author made an attempt to analyze the intuitive aspect of the philosophical works, which belong to the wider experience of „philosophical self-establishing” of the subject. The issues tackled by the author include the importance of the fundamental intuition in philosophy as a source of philosopher’s inspiration; intuitive (axiological) essence of the collective consciousness with its meaning in didactics; perceiving the sense of the intuition of existence as the intuition of „being” in the context of „transcending” the „being” by the subject. According to the author, the issue of intuition provides a great opportunity for the reflection on natural premises of philosophy, which are necessary for thinking about the most important aspects of people’s spiritual life. Initially intuitive and pre-logical horizon of meanings is perceived here as a framework for the diverse disciplines of philosophical cognition, which always explain one of the basic experiences of the human life.